2021
DOI: 10.1371/journal.ppat.1010116
|View full text |Cite
|
Sign up to set email alerts
|

VgrG-dependent effectors and chaperones modulate the assembly of the type VI secretion system

Abstract: The type VI secretion system (T6SS) is a spear-like nanomachine found in gram-negative pathogens for delivery of toxic effectors to neighboring bacterial and host cells. Its assembly requires a tip spike complex consisting of a VgrG-trimer, a PAAR protein, and the interacting effectors. However, how the spike controls T6SS assembly remains elusive. Here we investigated the role of three VgrG-effector pairs in Aeromonas dhakensis strain SSU, a clinical isolate with a constitutively active T6SS. By swapping VgrG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 61 publications
5
15
0
2
Order By: Relevance
“…Indeed, we show here that the MIX-effector, VPA1263, interacts with VgrG and not with two other T6SS structural components, Hcp and PAAR. The loading of MIX-effectors onto VgrG is further supported by a recent report that showed direct interaction between VasX, a MIX-effector from V. cholerae (Miyata et al, 2011), and its cognate VgrG (Liang et al, 2021). Nevertheless, although we expected to find that MIX plays a major role in mediating interaction with VgrG, we did not observe a dramatic difference in the VgrG binding ability between the full-length effector and a variant lacking the MIX domain.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Indeed, we show here that the MIX-effector, VPA1263, interacts with VgrG and not with two other T6SS structural components, Hcp and PAAR. The loading of MIX-effectors onto VgrG is further supported by a recent report that showed direct interaction between VasX, a MIX-effector from V. cholerae (Miyata et al, 2011), and its cognate VgrG (Liang et al, 2021). Nevertheless, although we expected to find that MIX plays a major role in mediating interaction with VgrG, we did not observe a dramatic difference in the VgrG binding ability between the full-length effector and a variant lacking the MIX domain.…”
Section: Discussionsupporting
confidence: 84%
“…We speculate that MIX contributes toward a stable or desirable effector conformation that is required for correct loading or positioning on the T6SS spike. Alternatively, following recent observations by Liang et al, who suggested that effectors interact with T6SS components, such as TssK and TssF, to fulfill the requirement for the "stuffing model" (Liang et al, 2021), it is possible that MIX plays a role in mediating the interaction of a spike-loaded effector with the T6SS base plate. Inconclusive results obtained during repeated attempts to detect a MIX-mediated interaction between VPA1263 and TssK prevent us from currently confirming or ruling out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…T6SS secretion in V. cholerae , A. dhakensis , Agrobacterium tumefaciens , and Enterobacter cloacae requires the presence of multiple VgrG-dependent effectors ( 17 , 28 , 31 , 32 ). The previously known T6SS requirement for a heterotrimer VgrG spike in V. cholerae and in A. dhakensis is tightly linked to the specific structural effects of effectors because a pseudohomotrimer VgrG spike made of VgrG chimeras, differing only by the C-terminal effector-loading tail, is functional for T6SS assembly ( 33 ). There is also direct interaction between effectors and the baseplate protein TssK and the assembly chaperone TssA ( 33 ).…”
Section: Commentarymentioning
confidence: 99%
“…The previously known T6SS requirement for a heterotrimer VgrG spike in V. cholerae and in A. dhakensis is tightly linked to the specific structural effects of effectors because a pseudohomotrimer VgrG spike made of VgrG chimeras, differing only by the C-terminal effector-loading tail, is functional for T6SS assembly ( 33 ). There is also direct interaction between effectors and the baseplate protein TssK and the assembly chaperone TssA ( 33 ). These findings not only suggest that the effector stuffing within the baseplate cavity is crucial for stabilizing T6SS assembly in these species but also lead to the hypothesis that the differential requirement for PAAR in different species may be dependent on PAAR-associated effectors.…”
Section: Commentarymentioning
confidence: 99%
“…Several experimental and computational approaches have been used to identify effector and immunity (E/I) pairs (2,7,11,12,29,(33)(34)(35)(36). Nevertheless, because T6SS effectors employ diverse mechanisms for secretion (13,(37)(38)(39), and therefore lack a canonical secretion signal, it is estimated that many more effectors still await discovery.…”
Section: Introductionmentioning
confidence: 99%